2021
DOI: 10.1371/journal.pone.0248685
|View full text |Cite
|
Sign up to set email alerts
|

Patient feedback surveys among pregnant women in Eswatini to improve antenatal care retention

Abstract: Background Uptake and retention in antenatal care (ANC) is critical for preventing adverse pregnancy outcomes for both mothers and infants. Methods We implemented a rapid quality improvement project to improve ANC retention at seven health facilities in Eswatini (October-December 2017). All pregnant women attending ANC visits were eligible to participate in anonymous tablet-based audio assisted computer self-interview (ACASI) surveys. The 24-question survey asked about women’s interactions with health facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…After applying QI solutions to identified quality-of-care challenges, we observed decreases in client wait time, reported stigma and VL result TAT, and increases in client satisfaction with wait time and service confidentiality. This highlights our system's effectiveness in improving HIV service quality at targeted facilities, echoing similar findings from other studies on the use of client-driven CQI models to address service quality gaps, such as the use of Community Score Cards to improve services to prevent perinatally acquired HIV in Malawi [19], use of electronic self-interviews integrated into rapid QI process to improve client−provider relationships in Eswatini [20] and use of CQI cycles to minimize service delays at HIV clinics in Kenya [9]. This service quality monitoring system also enabled IHAP-HK to more rapidly flag and deploy corrective measures to address service delivery and quality issues.…”
Section: Discussionsupporting
confidence: 75%
“…After applying QI solutions to identified quality-of-care challenges, we observed decreases in client wait time, reported stigma and VL result TAT, and increases in client satisfaction with wait time and service confidentiality. This highlights our system's effectiveness in improving HIV service quality at targeted facilities, echoing similar findings from other studies on the use of client-driven CQI models to address service quality gaps, such as the use of Community Score Cards to improve services to prevent perinatally acquired HIV in Malawi [19], use of electronic self-interviews integrated into rapid QI process to improve client−provider relationships in Eswatini [20] and use of CQI cycles to minimize service delays at HIV clinics in Kenya [9]. This service quality monitoring system also enabled IHAP-HK to more rapidly flag and deploy corrective measures to address service delivery and quality issues.…”
Section: Discussionsupporting
confidence: 75%
“…While many PCC approaches in the HIV space target HCW knowledge and skills [39–41], those that begin with understanding the HCW context will both position the HCW to adopt new practices by recognizing their existing efforts, and identify relational and organizational intervention targets that will enable individual‐level HCW change, supporting intervention appropriateness. Similarly, while our FGDs supported that providing information to HCWs to improve PCC [42–44] is acceptable, specific HCW responses demonstrate that the perceived relevance of the questions asked and the ability to identify HCW recourse to action in response to the information shared influences information appropriateness. Data use and actionability may be important intervention targets, particularly among non‐management‐level HCWs.…”
Section: Discussionmentioning
confidence: 63%
“…The study found that one of the biggest reasons of women' reluctance to complete 4 ANC standard visits is due to ignorance on the role of these visits. This is explained by some of them who responded that they believe that one or two ANC visits are sufficient, and others who need to be reminded on the date of ANC visit appointment because they are busy with other work and responsibilities.Studied showed that the husband should play an important role in motivating and reminding the wife to attend different ANC visits appointmentin this study, it was shown that it is necessary to raise awareness of pregnant women on the role of doing 4 ANC standard visits to the health of the mother and of the fetus [18]. The awareness on the health benefits of 4 standard ANC should be created on the husband not only for the wife.…”
Section: Discussionmentioning
confidence: 77%